Communicating in the highly regulated tobacco industry: the case of Philip Morris International - Carapinha, Luís Carlos Carvalho (2021)
This report was developed to study how legal regulations restrict the communication and promotional efforts of the tobacco industry, worldwide and in Portugal. The object of study chosen was the tobacco firm Philip Morris, mostly due to its attempts in the past to overcome industry’s boundaries, its historic importance regarding communication in Marketing, and its new product offering (IQOS). Tobacco consumption is declining in the world. Consumers are more educated, have more access to information and are more aware of what tobacco products do to their health. The IQOS comes as an answer to the health concerns of the modern tobacco consumer and to the dropping cigarettes’ market share, but also as a possible way for Philip Morris to communicate externally without so many restrictions – the firm looks into the future instead of relying on yesterday’s successful products and campaigns. In Portugal, Philip Morris has an immediate target of 610,000 to pitch the IQOS to – these are daily smokers, aged from 25 to 54, who want to change and improve their health. Philip Morris encourages every smoker to quit, but if they fail in such attempt the IQOS is there for them as a less harmful way to enjoy the tobacco taste and experience. To attract and retain that target and to spread the new positioning of Philip Morris some recommendations were proposed, which focused on achieving five communication objectives: increase/build brand awareness, change attitudes towards RRPs, establish need for RRPs, influence purchase intent, and retain existing customers (brand loyalty).